Efeitos da integração econômica no continente africano - Amann, Jean Carlo (Universidade do Vale do Rio dos Sinos, 2016)
This dissertation investigates the economic integration on the African continent, in the ex-post sense, as well as in the ex-ante sense. Firstly, to assess the economic effects of regional agreements already established, such as COMESA, ECOWAS and SADC, I apply a gravity model, with panel data and PMVP estimator (Poisson pseudo-maximum likelihood), for the 1995-2013 period. Lastly, to simulate a continental integration on Africa, analyzing the effects of such policy for the trade and for the welfare of the African countries, I apply the GTAP general equilibrium model (Global Trade Analysis Project), version 8, with products aggregate per technological intensity. The main findings, in respect to the already established agreements (ex-post analysis) is that COMESA and SADC were capable of enhancing the trade between its country members, with no evidences of trade diversion on the imports as well as on the exports (building blocks). The ECOWAS group, on the contrary, was not able to stimulate the trade of its members, showing trade diversion signs (stumbling block). On the estimation of the potential trade flows, in a general way, it was realized that the members of the three agreements traded more with each other than the predicted by the gravity model, referring to the natural trading partner’s concept and the Linder Hypothesis. On the ex-ante analysis, on both simulation with the GTAP general equilibrium model, the results point out to the welfare expansion on the African continent as a whole, through improvements on the allocative efficiency and gains on the terms of trade, besides the trade improvement on an intra-Africa basis, mostly on technological intensive products. On the restrictive trade liberalization scenario, the gains of the African countries are substantially minimized, indicating to the relevance of primary products for such continent.
Keywords: Integração econômica; África; Modelo gravitacional; Modelo GTAP; Economic integration; Africa; Gravity model; GTAP model; ACCNPQ::Ciências Sociais Aplicadas::Economia